Pigment epithelium‐derived factor restoration increases bone mass and improves bone plasticity in a model of osteogenesis imperfecta type VI via Wnt3a blockade. Issue 8 (28th April 2016) - Belinsky, Glenn S.; Sreekumar, Bharath; Andrejecsk, Jillian W.; Saltzman, W. Mark; Gong, Jingjing; Herzog, Raimund I.; Lin, Samantha; Horsley, Valerie; Carpenter, Thomas O.; Chung, Chuhan
ABSTRACT: Null mutations in for pigment epithelium‐derived factor (PEDF), the protein product of the SERPINF1 gene, are the cause of osteogenesis imperfecta (OI) type VI. The PEDF‐knockout (KO) mouse captures crucial elements of the human disease, including diminished bone mineralization and propensity to fracture. Our group and others have demonstrated that PEDF directs human mesenchymal stem cell (hMSC) commitment to the osteoblast lineage and modulates Wnt/β‐catenin signaling, a major regulator of bone development; however, the ability of PEDF to restore bone mass in a mouse model of OI type VI has not been determined. In this study, PEDF delivery increased trabecular bone volume/total volume by 52% in 6‐mo‐old PEDF‐KO mice but not in wild‐type mice. In young (19‐d‐old) PEDF‐KO mice, PEDF restoration increased bone volume fraction by 35% and enhanced biomechanical parameters of bone plasticity. A Wnt‐green fluorescent protein reporter demonstrated dynamic changes in Wnt/β‐catenin signaling characterized by early activation and marked suppression during terminal differentiation of hMSCs. Continuous Wnt3a exposure impeded mineralization of hMSCs, whereas the combination of Wnt3a and PEDF potentiated mineralization. Interrogation of the PEDF sequence identified a conserved motif found in other Wnt modulators, such as the dickkopf proteins. Mutation of a single amino acid on a 34‐mer PEDF peptide increased mineralization of hMSC cultures compared with the native peptide sequence. These results indicate that PEDF counters Wnt signaling to allow for osteoblast differentiation and provides a mechanistic insight into how the PEDF null state results in OI type VI.—Belinsky, G. S., Sreekumar, B., Andrejecsk, J. W., Saltzman, W. M., Gong, J., Herzog, R. I., Lin, S., Horsley, V., Carpenter, T. O., Chung, C. Pigment epithelium‐derived factor restoration increases bone mass and improves bone plasticity in a model of osteogenesis imperfecta type VI via Wnt3a blockade. FASEB J. 30, 2837‐2848 (2016). www.fasebj.org